Somatic BRCA Mutation in a Cholangiocarcinoma Patient for HBOC Syndrome Detection - Paradiso, Angelo Virgilio; Patruno, Margherita; Digennaro, Maria; Tommasi, Stefania; Pilato, Brunella; Argentiero, Antonella; Brunetti, Oronzo; Silvestris, Nicola (Frontiers in Oncology, 2020)
BRCA-associated hereditary breast and ovarian cancer syndrome (HBOC) is characterized by an increased risk to develop other malignancies including cholangiocarcinoma (CCA). Even if somatic BRCA mutations in CCA have been reported, its utilization as a proband case to individualize HBOC families has not been yet reported. Two healthy daughters of a death patient affected by methacronous CCA and breast cancer accessed to our Genetic Counselling with the aim to evaluate their cancer risk. We performed a somatic BRCA1/2 NGS analysis on DNA extracted from formalin-fixed, paraffin-embedded CCA-tissue of their mother. We identify a pathogenic variant c.6468_6469delTC in BRCA2 gene mutation. So far, we assessed germline BRCA mutation in the daughters, with the individuation of the same pathogenic variant in one of them. For the first time, we used a CCA somatic BRCA mutation to identify a family with HBOC